English-French translation : a practical manual - Gagne, Christophe; Wilton-Godberfforde, Emilia (London ; New York : Routledge, 2021)
"English-French Translation: A Practical Manual allows advanced learners of French to develop their translation and writing skills. This book provides a deeper understanding of French grammatical structures, the nuances of different styles and registers and helps increase knowledge of vocabulary and idiomatic language. The manual provides a wealth of practical tasks based around carefully selected extracts from the diverse text types students are likely to encounter; from literary and expository, to persuasive and journalistic. A mix of shorter targeted activities and lengthier translation pieces guide learners through the complexities and challenges of translation from English into French. This comprehensive manual is ideal for advanced undergraduate and postgraduate students in French language and translation"--
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Translating into French; English language -- Grammar, Comparative -- French; French language -- Grammar, Comparative -- English; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / French; LANGUAGE ARTS & DISCIPLINES / Journalism